Development and Evaluation of Multimedia Interventions to Promote Breast and Cervical Health among South Asian Women in Hong Kong: A Project Protocol - So, Winnie K. W. (Asia Pac J Oncol Nurs, 2017)
Recent studies conducted in the local community indicate that the uptake rates of breast and cervical cancer screening among South Asian ethnic minorities are lower than those of the general population. The development of interventions to promote these minorities’ awareness of breast and cervical health and the importance of cancer screening is therefore required. This study protocol aims to develop culturally sensitive multimedia interventions to promote awareness of breast and cervical cancer prevention among South Asian women in Hong Kong, and to evaluate the outcomes of such interventions using a Reach-Effectiveness-Adoption-Implementation-Maintenance framework. By using a multimedia approach and developing socio-culturally relevant and linguistically appropriate educational materials, information related to cancer and accessible preventive measures for breast and cervical cancer is expected to be disseminated more effectively among South Asian women and ultimately increase their awareness of engaging in healthy lifestyles and taking part in cancer screening tests. Successful engagement of community partners will enhance the future sustainability of the project.